Hubungan Diet Rendah Garam Dengan Tekanan Darah Pada Pasien Hipertensi - Saputri, Winda Puspita Regina; Umami, Vidhia; Hasibuan, Faizal Drissa (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Hypertension is a major global health problem, and high sodium intake is known to increase blood pressure by affecting fluid balance and vessel resistance. This study aims to examine the relationship between adherence to a low-salt diet and blood pressure control in patients with hypertension. A systematic review was conducted using ten articles published between 2020 and 2025 from Google Scholar and ScienceDirect. Article selection used simple keyword filtering related to diet and hypertension. Results: All reviewed studies showed a significant relationship between low-salt diet adherence and reduced blood pressure, with most reporting improvements within two to four weeks of sodium restriction. Low-salt diet adherence is closely associated with better blood pressure control, supporting its role as an effective non-pharmacological strategy in hypertension management.